2021
DOI: 10.1007/s11218-021-09612-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 triggered changes to instruction and assessment on university students’ self-reported motivation, engagement and perceptions

Abstract: During the northern hemisphere Winter 2020 academic term, university students had to adjust to remote learning in response to the COVID-19 pandemic. This abrupt change provided a unique opportunity to examine students’ motivation, engagement and perceptions of success and cheating under two learning conditions, namely traditional and remote. We used a single survey to collect retrospective self-report data from a convenience sample of Canadian undergraduate students ( n = 98) about their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
115
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 35 publications
10
115
3
8
Order By: Relevance
“…Our results indicate that a significant number of students felt that they were dropping out of school during the pandemic [ 23 ] and that negative feeling had a significant influence on psychological distress. Academic investment and affiliation may prevent anxiety and depression in students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that a significant number of students felt that they were dropping out of school during the pandemic [ 23 ] and that negative feeling had a significant influence on psychological distress. Academic investment and affiliation may prevent anxiety and depression in students.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals from disadvantaged family backgrounds are more likely to have unsupportive attitudes toward online courses and are therefore at risk of greater psychological distress when COVID-related restrictions are in place [21]. Although teacher and student characteristics influence the behavioral intention to use and accept e-learning systems [22], it would appear that students' achievements, engagement, and perceptions of success decreased during the pandemic overall [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many educational institutions conducted online surveys to evaluate the level of satisfaction of remote learning, the effectiveness of remote teaching, and to learn how students were coping with stress related to the COVID-19 pandemic (Aristovnik et al, 2020;Demuyakor, 2020). The results generally indicate several factors playing an important role in efficient remote studying: availability of a good quality Internet infrastructure and digital equipment, teaching staff support, computer skills in using remote learning platforms and programs, living conditions, as well as motivation, self-discipline, and self-initiative (Aristovnik et al, 2020;Daniels et al, 2021;Zhu et al, 2020). The effectiveness and the ease of implementation of remote learning depended much on the prevalence of this form of learning before the COVID-19 pandemic (Aristovnik et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…This study revealed lower satisfaction and usefulness of teaching methods during the COVID-19 pandemic. Evaluation of remote education in universities due to the COVID-19 pandemic has been reported in many studies worldwide [ 4 , 27 , 28 , 29 , 30 ]. A study in Canada observed a decrease in university students’ achievement goals, engagement, and perceptions of success, and an increase in perceptions of cheating [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of remote education in universities due to the COVID-19 pandemic has been reported in many studies worldwide [ 4 , 27 , 28 , 29 , 30 ]. A study in Canada observed a decrease in university students’ achievement goals, engagement, and perceptions of success, and an increase in perceptions of cheating [ 28 ]. In a study in India, a majority of students responded that they liked receiving remote education during the lockdown, but they reacted negatively toward maintaining the same education method after the lockdown was lifted, responding that the teaching method before the COVID-19 pandemic was better in many ways (i.e., topic understanding and net connectivity) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%